Panel2: Public Health Emergencies and Health Communication - Zhao, Xinjie (The Journal of Medicine, Humanity and Media, 2023)
Public emergencies are analogous to diseases in human society, representing both a genuine crisis and an opportunity for social development that necessitates collaborative responses from diverse perspectives. On November 4, 2023, the sixth International Academic Symposium on "Health, Humanities and Media," organized by Peking University’s School of Journalism and Communication, fostered an extensive discussion centered around the theme of "Health Communication in Public Emergencies". Chaired by Professor Xu Jing, director of the Master Program of Health Communication at Peking University’s School of Journalism and Communication, the symposium witnessed presentations and exchanges among ten scholars from various domestic and international universities who shared their latest achievements regarding the competence and credibility of authoritative entities in disseminating health information during public emergencies, emotional contagion and impact through social media platforms, management strategies for false health information dissemination as well as rumors.